Fecal Microbiota Transplantation Relieves Gastrointestinal and Autism Symptoms by Improving the Gut Microbiota in an Open-Label Study - Li, Ning; Chen, Hongyan; Cheng, Yi; Xu, Fenghua; Ruan, Guangcong; Ying, Senhong; Tang, Wen; Chen, Lu; Chen, Minjia; Lv, LinLing; Ping, Yi; Chen, Dongfeng; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Autism spectrum disorder (ASD) is a severe brain development disorder that is characterized by deficits in social communication and restricted, repetitive and stereotyped behaviors. Accumulating evidence has suggested that gut microbiota disorders play important roles in gastrointestinal symptoms and neurodevelopmental dysfunction in ASD patients. Manipulation of the gut microbiota by fecal microbiota transplantation (FMT) was recently shown to be a promising therapy for the treatment of various diseases. Here, we performed a clinical trial to evaluate the effect of FMT on gastrointestinal (GI) and ASD symptoms and gut microbiota alterations in children with ASD. We found that there was a large difference in baseline characteristics of behavior, GI symptoms, and gut microbiota between children with ASD and typically developing (TD) control children. FMT could improve GI symptoms and ASD symptoms without inducing any severe complications. Similarly, FMT significantly changed the serum levels of neurotransmitters. We further observed that FMT could promote the colonization of donor microbes and shift the bacterial community of children with ASD toward that of TD controls. The abundance of Eubacterium coprostanoligenes pre-FMT was positively correlated with high GSRS scores, whereas a decrease in Eubacterium coprostanoligenes abundance induced by FMT was associated with the FMT response. Our data suggest that FMT might be a promising therapeutic strategy to improve the GI and behavioral symptoms of patients with ASD, possibly due to its ability to alter gut microbiota and highlight a specific microbiota intervention that targets Eubacterium coprostanoligenes that can enhance the FMT response. This trial was registered at the Chinese Clinical Trial Registry (www.chictr.org.cn) (trial registration number ChiCTR1800014745).